SIMPLE COST EFFECTIVE STABILITY INDICATING METHOD DEVELOPMENT FOR THE ESTIMATION OF HALCINONIDE AND NEOMYCIN USING RP-HPLC (CAHIERS MAGELLANES-NS, 2024)
This study presents the development of a simple, cost-effective stability-indicating RP-HPLC method for the analysis of Halcinonide (HCN) and Neomycin (NMC). The method was optimized for specificity, linearity, and system suitability. Chromatographic analysis demonstrated that the method could effectively distinguish between HCN, NMC, and any potential interfering substances, as shown in the chromatograms of both blank and drug samples. The linearity of the method was confirmed with correlation coefficients of 0.999 for both HCN and NMC, indicating a strong linear relationship between concentration and peak area. System suitability tests showed acceptable results, with retention times, peak areas, and tailing factors falling within the recommended ranges for both compounds. Additionally, response ratio analysis further validated the method’s precision and reliability. This RP-HPLC method provides an effective tool for the stability testing and quality control of HCN and NMC, ensuring accurate and consistent results at a minimal cost.